LOVASTATIN EFFECT ON VASCULAR REMODELING AND MYOCARDIAL SYSTOLIC AND DIASTOLIC FUNCTION IN PATIENTS WITH STABLE ISCHEMIC HEART DISEASE - A. S. Kerimkulova; A. M. Noruzbaeva; O. S. Lunegova; B. Z. Imanov; M. A. Pavlenko; A. E. Mirrahimov; I. JU. Gottfried; E. M. Mirrahimov (Столичная издательская компания, 2016)
Aim. To study effect of 12-month therapy with lovastatin on vascular remodeling, systolic and diastolic functions of left ventricle (LV).Material and methods. 84 patients (54,3±6,5 y.o.) with ischemic heart disease (IHD) and dislipoproteinemia were involved in the study. Patients were randomized into 2 groups. Patients of the 1st group (n=44) received lovastatin (20-60 mg daily) in addition to hypolipidemic diet and standard therapy. Patients of the 2nd group (n=39) were treated with diet and standard therapy only. Lipid spectrum and transaminase blood levels estimation, carotid duplex ultrasonography, echocardiography were performed initially and after 12 months of treatment.Results. Decrease of carotid intima-media thickness, delay of increasing of LV myocardium mass index, increase of LV ejection fraction was observed in 12 months of treatment in patients of the 1st group. There were not any changes of LV diastolic function in both groups.The conclusion. In patients with IHD and dislipoproteinemia 12 month lovastatin therapy prevents of vascular remodeling and improves LV systolic function.